Nonlinear Ultrasonic Characterization for Intergranular Corrosion Susceptibility of 304 Austenitic Stainless Steel - HOU Tian-yu; LI Ping; CHEN Lei; ZHAO Jie; LI Ting-ju (Cailiao gongcheng, 2017)
The variation law of nonlinear ultrasonic parameters for the samples sensitized at 650℃ for 2, 6, 10h was discussed using nonlinear ultrasonic testing technique and XRD pattern as well as microstructure. The results indicate that normalized nonlinear parameters(β/β0) of the samples show a monotonous growth trend with the increase of the sensitized time, and normalized nonlinear parameters(β/β0) of the samples sensitized with 2,6,10h increase to 28%, 32% and 43% respectively compared with that of the base material, meaning that it is feasible to use nonlinear parameter to characterize the sensitivity degree. It is analyzed that the mismatch between the carbide (Cr23C6) precipitated on the grain boundary and the austenitic matrix causes the local strain fields which interfere with the propagation of ultrasonic wave in the solid sample. In addition, the increment of precipitation phase exacerbates further the distortion of the ultrasonic with prolonging of the sensitization time.